The interpretation and objective criteria for determining child support based on «successful studies» - Baldino Mayer, Nicolás (2021)
This article has two objectives: to clarify the meaning of successful studies in the context of child support for children over 18 years of age and to define objective criteria for its provision and quantification. To this end, first of all, we will differentiate the nature of such a pension with respect to that held by minors and incapable adult children; subsequently, we will perform an axiological analysis and interpret the rules of the Civil Code involved in a literal, systematic and teleological manner. Finally, the incidence of the concept of «state of necessity» and the economic capacity of the obligor will be evaluated. The importance of this work lies in providing simple and clear criteria that facilitate argumentation and uniformity in judicial decisions.